Rediscovery of the enigmatic Stenosternus costatus Karsch (Coleoptera: Scarabaeidae: Orphninae) from São Tomé Island - Frolov, Andrey V.; Akhmetova, Lilia A. (Zootaxa, 2015)
Stenosternus Karsch, 1881 is one of the least-known genera of the Orphninae scarab beetles. It was described from a single specimen of the odd-looking S. costatus Karsch, 1881, from the island of São Tomé, Gulf of Guinea, West Africa. Karsch (1881) originally placed Stenosternus in the “Copridae” but later moved it to the Orphninae (Karsch, 1887). Since then, no more findings of S. costatus have been reported. The genus was redescribed by Frolov (2013) from the holotype of S. costatus and provisionally placed in the tribe Aegidiini Paulian based on a number of putative synapomorphies (Frolov, 2012). However, the material limited to only one male specimen did not allow the author to clarify which of its unique characters might be malformations or be sex dependent.